Is there a familial association between obstructive sleep apnoea/hypopnoea and the sudden infant death syndrome?. Issue 4 (26th March 2004) - Vennelle, M; Brander, P E; Kingshott, R N; Rees, K; Warren, P M; Keeling, J W; Douglas, N J
Abstract : Background: One postulated cause of the sudden infant death syndrome (SIDS) is upper airway obstruction during sleep. Several studies have suggested that SIDS may be more common in families with obstructive sleep apnoea/hypopnoea syndrome (OSAHS), but were limited by uncertainty as to whether the deaths were due to SIDS. We have tested the hypothesis that parents of true SIDS cases have an increased frequency of apnoeas and hypopnoeas during sleep. Methods: The parents of 269 rigorously determined SIDS cases were invited for single night polysomnography and daytime ventilatory control measurement. Results: Parents of 198 cases were identified but 152 did not respond or declined. Fifty five parents of 34 cases were studied and matched for age, height, and weight to 55 subjects from general practice registers. There was no difference in breathing during sleep between the parents of SIDS cases (median (IQR) 5.9 (3.2, 10.7) apnoeas+hypopnoeas/h) and controls (6.7 (4.0, 12.2) apnoeas+hypopnoeas/h; p = 0.47), but the SIDS parents had lower minimum nocturnal oxygen saturation (median (IQR) 92 (89, 93)%) than controls (92 (90, 94)%; p = 0.048). There were no major differences in control of breathing when awake between SIDS parents and controls. Conclusions: These results provide no evidence to support an association between SIDS and OSAHS. However, the minor impairment of oxygenation during sleep in SIDS parents requires further study.